SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPPLIER KOPI TERBAIK KEDAI KOPI SAKA MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Setiadji Setiadji; Missi Hikmatyar; Yusuf Sumaryana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The selection of the best coffee supplier is a critical factor in ensuring the operational success and quality of products offered by Kedai Kopi Saka. A systematic and objective evaluation process is needed to identify the most suitable supplier that meets various criteria such as product quality, price, delivery punctuality, production capacity, and service quality. This study aims to develop a decision support system (DSS) using the Simple Additive Weighting (SAW) method to assist Kedai Kopi Saka in selecting the best coffee supplier. The SAW method is employed due to its ability to handle multiple criteria and weight assignments, enabling a comprehensive evaluation of suppliers. The system evaluates suppliers based on predefined criteria, assigns weights to each criterion, normalizes the values, and calculates the final scores to rank the suppliers. The results of this system provide clear and reliable recommendations for decision-makers. The implementation of this decision support system ensures a more transparent, efficient, and accurate supplier selection process. Furthermore, this system contributes to improving the decision-making process at Kedai Kopi Saka and supports its goal of maintaining high-quality coffee offerings for its customers.